Nationalization as credible threat against tacit collusion - Flavio Delbono; Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
Within a simple model of differentiated oligopoly, we show that tacit collusion may be prevented by the threat of nationalising a private firm coupled with the appropriate choice of the weight given to private profits in the maximand of the nationalised company. We characterise the properties of such a threat and prove that it may allow to credibly deter tacit collusion.
Keywords: H13; L13; L32; 330